“Serrana”. Una experiencia de cortometraje - Zirena Arana, Valeria (2019)
“Serrana” is a short film melodrama genre based on real events. In order to preserve the narrative as true as possible to the life story of Rosario, this short film was made in the Pomata district, located in the Department of Puno and in the Rimac district, located in Lima, capital of Peru. Also, fort the scenes of the altiplano, we worked with non-professional actors who speak the aymara language. Finally, my intention is to present a story that will lead us to reflect on forced migration and violence against women, where poverty, suffering and discrimination are present.